Thorndike's Law 2.0: Dopamine and the Regulation of Thrift - Beeler, Jeff A. (Frontiers in Neuroscience, 2012)
Dopamine is widely associated with reward, motivation and reinforcement learning. Research on dopamine has emphasized its contribution to compulsive behaviors, such as addiction and overeating, with less examination of its potential role in behavioral flexibility in normal, non-pathological states. In the study reviewed here, we investigated the effect of increased tonic dopamine in a two-lever homecage operant paradigm where the relative value of the levers was dynamic, requiring the mice to constantly monitor reward outcome and adapt their behavior. The data were fit to a temporal difference learning model that showed that mice with elevated dopamine exhibited less coupling between reward history and behavioral choice. This work suggests a way to integrate motivational and learning theories of dopamine into a single formal model where tonic dopamine regulates the expression of prior reward learning by controlling the degree to which learned reward values bias behavioral choice. Here I place these results in a broader context of dopamine’s role in instrumental learning and suggest a novel hypothesis that tonic dopamine regulates thrift, the degree to which an animal needs to exploit its prior reward learning to maximize return on energy expenditure. Our data suggest that increased dopamine decreases thriftiness, facilitating energy expenditure and permitting greater exploration. Conversely, this implies that decreased dopamine increases thriftiness, favoring the exploitation of prior reward learning and diminishing exploration. This perspective provides a different window onto the role dopamine may play in behavioral flexibility and its failure, compulsive behavior.